2015
DOI: 10.13181/mji.v24i1.1191
|View full text |Cite
|
Sign up to set email alerts
|

Palmaris longus absence in six largest Indonesian ethnicities and its relationship with gender, ethnicity, and hand dominance

Abstract: ABSTRAK ABSTRACTBackground: Palmaris longus (PL) tendon is often used as graft in tendon or ligament reconstruction. PL absence is a normal variation in human body. Its prevalence was different in various population. Serbian population had an absence rate of 42.4%, but in the Korean population it was only 4.0%. This study aimed to determine the prevalence of PL absence in various ethnic of Indonesian population and its relationship with gender and side of hand dominance. Methods:We conducted a cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The present study demonstrated that bilateral absence of PL tendon was common in female (14.2%) than in male (10.7%) and these findings coincided with findings of various studies conducted among different populations. 18,23,26,29 In relation to the handedness, left palmaris longus agenesis was more common in female left handed individuals (45.4%) than in male (15.4%) which was similar with the studies conducted in Serbia and Greece. 24,27 The similar study had also stressed to the fact that there was a strong correlation between palmaris longus agenesis and left hand dominance.…”
Section: Discussionsupporting
confidence: 84%
“…The present study demonstrated that bilateral absence of PL tendon was common in female (14.2%) than in male (10.7%) and these findings coincided with findings of various studies conducted among different populations. 18,23,26,29 In relation to the handedness, left palmaris longus agenesis was more common in female left handed individuals (45.4%) than in male (15.4%) which was similar with the studies conducted in Serbia and Greece. 24,27 The similar study had also stressed to the fact that there was a strong correlation between palmaris longus agenesis and left hand dominance.…”
Section: Discussionsupporting
confidence: 84%
“…15 Okafor et al documented that the tendon of PL is frequently used as graft for hand and reconstructive plastic surgeries. 4 The use of PL tendon has also been stated in the ligaments and tendon surgeries 17 along with chin and lip restoration procedures. 5 The insight about PL muscle is of vital importance for physicians, radiologists, physiotherapists and surgeons.…”
Section: P R O V I S I O N a L L Y A C C E P T E D F O R P U B L I C A T I O Nmentioning
confidence: 99%